Methodological challenges in designing efficacious drug abuse and HIV preventive interventions for hispanic adolescent subgroups - Pantin, Hilda (Springer-Verlag, 2005)
This article focuses on designing and evaluating drug abuse and HIV prevention interventions for subgroups of Hispanic adolescents. It describes the need for preventive interventions designed or adapted specifically for Hispanic adolescents and offers a rationale for subgrouping Hispanic adolescents based on risk and protective factor profiles rather than demographic indices. This subgrouping method is based on intrapersonal and ecodevelopmental domains of risk and protection. Finally, the article presents methods for designing, adapting, and evaluating “flexible” interventions for use with Hispanic adolescent subgroups.